2008
DOI: 10.1063/1.2825647
|View full text |Cite
|
Sign up to set email alerts
|

High-performance carbon nanotube coatings for high-power laser radiometry

Abstract: Radiometry for the next generation of high-efficiency, high-power industrial lasers requires thermal management at optical power levels exceeding 10 kW. Laser damage and thermal transport present fundamental challenges for laser radiometry in support of common manufacturing processes, such as welding, cutting, ablation, or vaporization. To address this growing need for radiometry at extremely high power densities, we demonstrate multiwalled carbon nanotube (MWCNT) coatings with damage thresholds exceeding 15 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…This to ensure the thermal and laser damage threshold is higher than SWCNTs. [24], [25] As far as the authors known, there are only few works reported regarding the usage of MWCNTs as saturable absorber in fibre laser application. For instance, Zhang et al [23] employs MWCNTs as saturable absorber for mode locking of neodymium-doped yttrium vanadate (Nd:YVO4) laser.…”
Section: Introductionmentioning
confidence: 99%
“…This to ensure the thermal and laser damage threshold is higher than SWCNTs. [24], [25] As far as the authors known, there are only few works reported regarding the usage of MWCNTs as saturable absorber in fibre laser application. For instance, Zhang et al [23] employs MWCNTs as saturable absorber for mode locking of neodymium-doped yttrium vanadate (Nd:YVO4) laser.…”
Section: Introductionmentioning
confidence: 99%
“…Further details of the experimental setup are described elsewhere. 8,12,13 Figures 1͑A͒ and 1͑B͒ show images of the exposed grids of SWCNTs and MWCNTs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The beam was focused on an area of ϳ0.25 mm 2 , and the scattered light was analyzed by the use of a 270 mm grating spectrometer. 8,12 For the electron microscopy analysis, the copper substrate was directly attached to the electron microscope sample holder by using carbon tape. Information from the Raman spectra was tabulated to assist in correlation with the structural changes observed by the use of electron microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations